2020
DOI: 10.1136/neurintsurg-2020-016766
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular thrombectomy in patients with large core ischemic stroke: a cost-effectiveness analysis from the SELECT study

Abstract: BackgroundIt is unknown whether endovascular thrombectomy (EVT) is cost effective in large ischemic core infarcts.MethodsIn the prospective, multicenter, cohort study of imaging selection study (SELECT), large core was defined as computed tomography (CT) ASPECTS<6 or computed tomography perfusion (CTP) ischemic core volume (rCBF<30%) ≥50 cc. A Markov model estimated costs, quality-adjusted life years (QALYs) and the incremental cost-effectiveness ratio (ICER) of EVT compared with medical management (MM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The results of ongoing RCTs testing EVT in patients with low ASPECTS in a 0-24 hours time window, regardless of the imaging modality, will be of particular interest to assess the relative effect of low ASPECTS and the delay from onset to reperfusion on the PH risk and its impact on functional recovery. 18,19 Overall, our results underline the importance of an expedited transfer of patients with suspected LVO-AIS to the cath lab to reduce the delay from onset to reperfusion, encouraging the use mobile stroke unit and the completion of RCT testing direct transfer to the angio suite. 20,21 Our study suffers from several limitations inherent to its design.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of ongoing RCTs testing EVT in patients with low ASPECTS in a 0-24 hours time window, regardless of the imaging modality, will be of particular interest to assess the relative effect of low ASPECTS and the delay from onset to reperfusion on the PH risk and its impact on functional recovery. 18,19 Overall, our results underline the importance of an expedited transfer of patients with suspected LVO-AIS to the cath lab to reduce the delay from onset to reperfusion, encouraging the use mobile stroke unit and the completion of RCT testing direct transfer to the angio suite. 20,21 Our study suffers from several limitations inherent to its design.…”
Section: Discussionmentioning
confidence: 62%
“…They also suggest that initial imaging by CT was by comparison with MRI associated with an higher rate of PH after adjustment on ASPECTS. The results of ongoing RCTs testing EVT in patients with low ASPECTS in a 0–24 hours time window, regardless of the imaging modality, will be of particular interest to assess the relative effect of low ASPECTS and the delay from onset to reperfusion on the PH risk and its impact on functional recovery 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…However, reperfusion failed to reach statistical significance with regards to absolute NIHSS score change if rCBV was high. These findings underline the ongoing debate on how and when to apply different neuroimaging tools for selection of patients who may benefit from EVT in the subgroup of those with low ASPECTS [13–15]. The HERMES meta‐analysis observed a benefit of EVT only in the subgroup of patients with ASPECTS of 3, whereas no treatment effect of MT was observed in patients with ASPECTS 0–2 or ASPECTS 4–5 [16], emphasizing the need for further diagnostic tools to reliably identify patients with low ASPECTS who are likely to benefit from EVT [3, 17].…”
Section: Discussionmentioning
confidence: 93%
“…A previous systematic review25 and two recent studies in the USA26 27 have demonstrated cost-effectiveness of endovascular thrombectomy for acute ischemic stroke. The ICER of coiling found in our study on aSAH was slightly higher than that (US$1236) of video-electroencephalography monitoring, which has been adopted for insurance coverage in epilepsy surgery candidates in Thailand 28.…”
Section: Discussionmentioning
confidence: 99%